Clinical parameters associated with obesity outcomes in vulnerable adolescents (Research, Society and Development, 2021)
Objective: Overweight and obesity rates are growing at alarming levels worldwide. Adolescents of higher socioeconomic status are more likely to be overweight, however, information from economically vulnerable populations is lacking. Therefore, the present study aimed to determine the impact of normative and self-perceived clinical aspects on the outcomes of obesity in vulnerable adolescents. Methodology: Observational cross-sectional study with 239 adolescents with an average age of 13 years, enrolled in public schools in Sabará (Minas Gerais). Body Mass Index values were obtained and classified according to AnthroPlus software. Dental Health Component of the Index of Orthodontic Treatment Need (IOTN) evaluated the normative malocclusion and the Aesthetic Component of IOTN the subjective occlusal evaluation. DMFT index evaluated dental caries activity and experience. Crude Odds Ratio values were estimated and adjusted, with a 95% confidence interval and a 5% significance level. Results: Adolescents with self-perceived malocclusion were less likely to be obese (P 0.05). Conclusion: Adolescents with self-perceived malocclusion were less likely to be obese, suggesting that obesity is associated with perceived malocclusion, but not with caries experience.